Transformasi Pernikahan Tidak Tercatat di Perbatasan - Bulan, Wahidah R. (Jurnal Bina Praja, 2021)
Undocumented marriage is a social reality prevalent in many communities, including in Tawau (Sabah, Malaysia), where several Indonesian workers make a living. Examining the process of interrelation structure and agency institutionalizing the practice of undocumented marriage through the depiction of the transformation process and the actors that play a role, the study is intended to obtain comprehensive information on why cases continue to occur even to the third generation. The study also identified the impact of unregistered marriages on migrant workers and their families to obtain a measurable picture of the gravity of the problem. As for the reason why Tawau was taken as the locus, considering that cases of undocumented marriage were quite high in the region. Using a case study type qualitative approach with data collection techniques through in-depth interviews and document studies (books, journals, reports, and mass media coverage), the results showed that the marriage process is not recorded as having transformed from generation to generation, which is marked by a decrease in structural strength—and strengthening the roles and abilities of actors to escape structural forces. As a result, the practice of unregistered marriage continues to increase. It is increasingly difficult to stop, although, on the other hand, the real impact of excess marriage is not recorded for the object, especially their children who have difficulty getting educational services. Government efforts to reduce the impact have been made. Unfortunately, it will lose meaning if the increase in unregistered marriages is not stopped.